Low socioeconomic status of a patient's residential area is associated with worse prognosis after acute myocardial infarction in Sweden. (1st March 2015) - Bergström, Göran; Redfors, Björn; Angerås, Oskar; Dworeck, Christian; Shao, Yangzhen; Haraldsson, Inger; Petursson, Petur; Milicic, Davor; Wedel, Hans; Albertsson, Per; Råmunddal, Truls; Rosengren, Annika; et al.
Abstract: Introduction: Previous studies have established a relationship between socioeconomic status (SES) and survival in coronary heart disease. Acute cardiac care in Sweden is considered to be excellent and independent of SES. We studied the influence of area-level socioeconomic status on mortality after hospitalization for acute myocardial infarction (AMI) between 1995 and 2013 in the Gothenburg metropolitan area, which has little over 800, 000 inhabitants and includes three city hospitals. Methods: Data were obtained from the SWEDEHEART registry (Swedish Websystem for Enhancement of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies) and the Swedish Central Bureau of Statistics for patients hospitalized for ST-elevation myocardial infarction (STEMI) and non-STEMI in the city of Gothenburg in Western Sweden. The groups were compared using Cox proportional hazards regression and logistic regression. Results: 10, 895 (36% female) patients were hospitalized due to AMI during the study period. Patients residing in areas with lower SES had higher rates of smoking and diabetes (P < 0.001), and were also at increased risk of developing complications, including heart failure and cardiogenic shock (P < 0.05). Living in an area with lower SES associated with increased risk of dying after an AMI also in models adjusted for risk factors (P < 0.05). Conclusion: Also in a country with strong egalitarian traditions, lower SES associates with worse prognosis after AMI, an association that persists after adjustments for differences in traditional cardiovascular risk factors.